2007
DOI: 10.1097/01.ccm.0000259463.33848.3d
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a bundle of quality indicators for the early management of severe sepsis and septic shock is associated with decreased mortality*

Abstract: Implementation of a severe sepsis bundle using a quality improvement feedback to modify physician behavior in the emergency department setting was feasible and was associated with decreased in-hospital mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
317
1
24

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 492 publications
(358 citation statements)
references
References 32 publications
16
317
1
24
Order By: Relevance
“…[4][5][6] Following such evidence-based protocols and process-of-care interventions has been shown to be associated with better patient outcomes, including decreased mortality. 7,8 Most patients with severe sepsis are cared for in intensive care units (ICUs). At times, there are no beds available in the primary ICU and patients presenting to the hospital with sepsis are cared for in other units.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Following such evidence-based protocols and process-of-care interventions has been shown to be associated with better patient outcomes, including decreased mortality. 7,8 Most patients with severe sepsis are cared for in intensive care units (ICUs). At times, there are no beds available in the primary ICU and patients presenting to the hospital with sepsis are cared for in other units.…”
Section: Discussionmentioning
confidence: 99%
“…A partir de entonces, se han corroborado los beneficios de esta estrategia de reanimación en múltiples estudios (9,10,(14)(15)(16)(17). A pesar de los hallazgos y de ser una estrategia recomendada en las guías internacionales y por importantes sociedades e instituciones, es preocupante ver la poca observancia a las guías detectada en diferentes sitios del mundo.…”
Section: Discussionunclassified
“…La escasa observancia de dichas recomendaciones demuestra la dificultad de trasladar los conocimientos a la práctica (7,10).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…That discovery ushered in an exciting era of early identification, resuscitation and monitoring of patients with sepsis. Since 2003, EGDT has been recommended in international sepsis guidelines [2][3][4], and implementation in routine care has been associated with benefits [5]. Likewise, many observers suggested that prompt recognition and treatment of sepsis may partly explain declining mortality from sepsis [6,7].…”
mentioning
confidence: 99%